Pola Asuh Orang Tua Dalam Motivasi Belajar Anak - Wardatul Asfiyah (Edification Journal : Pendidikan Agama Islam, 2020)
The process of interaction between parents and children includes activities such as educating, maintaining, protecting and directing children's behavior. During development, children learn from their parents. Parents teach various things to their children ranging from talking, walking and so forth. This article aims to describe parenting patterns in motivating children's learning. The method used in this paper is the library research method. The results of this study indicate that the motivation of children will be good if the parenting is done by good parents. The better parenting that parents do, the better the child's motivation to learn. Authoritative parenting (parenting that really gives attention to their children) becomes one of good parenting in fostering children's learning motivation than other parenting.